FISH-deletion mapping defines a 270-kb short stature critical interval in the pseudoautosomal region PAR1 on human sex chromosomes - Rao, Ercole; Weiß, Birgit; Fukami, Maki; Mertz, Andrea; Meder, J.; Ogata, Tsutomu; Heinrich, Udo; Garcia-Heras, J.; Schiebel, Katrin; Rappold, Gudrun (Human genetics, 1997)
Deletions of the pseudoautosomal region (PAR1) of the sex chromosomes have recently been discovered in individuals with short stature, and a minimal common deletion region of 700 kb within PAR1 has subsequently been defined. We have cloned this entire region, which is bounded by the Xp/Yp telomere, as an overlapping cosmid contig. In the present study, we have used fluorescence in situ hybridization (FISH) to study four patients with X-chromosomal rearrangements, two with normal height and two with short stature. Genotype-phenotype correlations have narrowed down the the critical “short stature interval” to a 270-kb region containing the gene with an important role in growth. A minimal tiling path of 6-8 cosmids bridging this interval is now available for interphase and metaphase FISH and provides a valuable tool for diagnostic investigations of patients with idiopathic short stature.
Gesehen am 30.03.2021